Analysis of the Quality of the Pre-Investment Phase based on the Process Approach - Aguilera-García, Luis Alexis (2022)
The pre-investment phase constitutes the information base of any project. Given the influence of this phase on the execution and subsequent exploitation of the investment, as well as its complex, iterative and dynamic nature, the deployment of the process approach is convenient in order to satisfy the relevant stakeholders. However, in the consulted literature there is no evidence of a detailed analysis of the structure of this phase as a process, and from the methodological point of view, insufficiencies in the evaluation and improvement of quality are identified, an aspect that limits its orientation towards the satisfaction of the parties. relevant stakeholders, which constitutes the problem to be solved in this investigation. The objective is focused on defining the configuration of the pre-investment phase as a process, based on the identification of its inputs, transformations, outputs, as well as the sub-processes that comprise it and the interrelationships between them. As a result, a methodology is presented that manages to operationalize the evaluation and improvement of the quality of the process and is composed of three stages and nine steps that contain three specific procedures, with the use of various tools, quality indices, the specific map and the process sheets.